Transformasi Digital pada UMKM dalam Meningkatkan Daya Saing Pasar - Novi Algi Alviani; Munawaroh Munawaroh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The phenomenon of digital transformation in MSMEs can be observed from several aspects, including: resource challenges during digital transformation because transformation, like any change, requires resources. Another phenomenon is organizational barriers: such as limited digital literacy, resistance to change, lack of skilled labor, limited capital, infrastructure, and technological barriers due to lack of knowledge. Apart from that, the lack of managerial support, a limited digital ecosystem, as well as concerns about data security and trust in technology are also obstacles. The technique for analyzing data in this research uses a literature review study. The research results show that there are multiple opportunities and attention for MSMEs, where there is a special need for MSMEs to carry out digital transformation in order to increase business competitiveness and expand market share. With digital transformation, the processes and operations of product downstreaming from producers to consumers will increase, speed of service, better trust, secure data exchange platforms, but also an opportunity for digital transformation to increase competitive advantage and expand market reach, increase operational efficiency. because it reduces time and costs for business activities, and increases market access.